Social experience and social cohabitation with mating promote spinogenesis in the nucleus accumbens of adult female prairie voles (Microtus ochrogaster) - Analía E. Castro; Marco A. López-Quiroz; Daniela Ávila-González; Francisco J. Camacho; Raúl G. Paredes; Néstor F. Díaz; Wendy Portillo (PLoS ONE, 2025)
Prairie voles ( Microtus ochrogaster) are monogamous rodents that establish life-long pair-bonds and display characteristic social and biparental care behaviors. Since social and sexual experiences modulate brain plasticity, the present study aimed to elucidate in female voles if social exposure to a male or social cohabitation with mating, which leads to pair-bonding, modulates spinogenesis processes in the medium spiny neurons (MSNs) in the nucleus accumbens (NAc). Females were randomly assigned to one of the following groups: 1) control (C), voles that cohabited with a familiar female in a clean cage; 2) social exposure (SE), voles housed in a cage divided into two equal compartments by an acrylic screen with small holes. The experimental female was placed in one of the compartments, and a male in the opposite one. Therefore, females were exposed to sensory cues from an adult male. Still, physical contact and copulation were not allowed, and 3) social cohabitation with mating (SCM) females were allowed to mate to induce pair-bonds. The NAc core and shell were processed for Golgi-Cox staining. Our results showed that MSN from SE and SCM groups had higher spine density than C females and a differential density of spine subtypes in the core and shell. Furthermore, only the SE condition induced an increment in MSN dendritic length and arborization in the core and shell regions. These findings demonstrate that males’ sexual cues and mating that promote pair-bonding modulate spinogenesis in the NAc and contribute to understanding the neuronal plasticity mechanism involved in pair-bonding in prairie voles.